2011
DOI: 10.1590/s0100-06832011000600029
|View full text |Cite
|
Sign up to set email alerts
|

Erosão em entre sulcos em área cultivada com cana crua e queimada sob colheita manual e mecanizada

Abstract: Although a number of studies related to environmental issues address air pollution, the increased use of biotechnology and mechanical harvesting of sugar cane, less attention has been paid to the negative environmental impacts caused by laminar erosion. This study aimed to determine the levels of organic matter (OM) and nutrients (P, K, Ca and Mg)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 34 publications
4
27
0
11
Order By: Relevance
“…The reduction of these areas is a result of the decrease in sediment concentration in runoff, which carries off the nutrients, due to the straw left after mechanical harvesting. Garbiate et al (2011) found a 7.6-fold lower sediment concentration in runoff from green than from burnt cane.…”
Section: (2009)mentioning
confidence: 84%
See 1 more Smart Citation
“…The reduction of these areas is a result of the decrease in sediment concentration in runoff, which carries off the nutrients, due to the straw left after mechanical harvesting. Garbiate et al (2011) found a 7.6-fold lower sediment concentration in runoff from green than from burnt cane.…”
Section: (2009)mentioning
confidence: 84%
“…The cultivation system with mechanical tillage and crop residue burning increases the amount of loose sediments carried away by runoff (Bertol et al, 2010). In the other system, the green cane residues form a soil cover that reduces aggregate destruction in the soil surface layer by the lower impact of raindrops on the surface (Garbiate et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Sendo este material, portanto, constituído não por agregados, mas por torrões de solo. Segundo Garbiate et al (2011) os efeitos da pressão exercida pelo tráfego de máquinas podem ser minimizados por meio da estabilidade estrutural associada à cobertura com resíduos vegetais. Como foi constatado por esses autores, o sistema de colheita mecanizada de cana crua apresentou maiores valores de DMG e DMP comparados aos sistemas de colheita mecanizada de cana queimada.…”
Section: Resultsunclassified
“…Por outro lado, alguns trabalhos mostraram que o intenso tráfego de colheitadora e do veículo de transbordo usados na colheita da cana sem a queima e mecanizada pode compactar e desorganizar a estrutura do solo, comprometendo as propriedades físicas e afetando a infiltração e retenção de água no solo (Souza et al, 2005;Leme Filho, 2009;Oliveira et al, 2010;Silva et al, 2012). Porém, a cobertura do solo com os resíduos vegetais da colheita pode contrapor-se ao efeito da compactação pelo maquinário e favorecer a estabilidade estrutural (Lado et al, 2004;Braida et al, 2006;Garbiate et al, 2011). Braida et al (2006) também afirmam que pela baixa densidade associada à susceptibilidade à deformação e elasticidade a palhada da cana depositada sobre o solo atenua as cargas aplicadas e dissipa em até 30% a energia de compactação.…”
Section: Atributos Físicos Do Solounclassified
“…A maioria dos estudos conclui que a eliminação da queima da palhada aumenta a quantidade de MO no solo favorecendo os atributos físicos, como relatado por Blair (2000) Garbiate et al (2011). Esses autores ressaltam a importância de preservar a palhada em lavouras de cana para manutenção e melhoria das propriedades físicas, sobretudo em solos de tabuleiros em que a compactação associada ao caráter coeso (adensamento natural) pode comprometer suas características físico-hídricas e reduzir a eficiência dos sistemas de produção agrícola da cana-de-açúcar.…”
Section: Atributos Físicos Do Solounclassified